Revolution in the Echo Chamber: Audio Drama's Past, Present and Future, Leslie Grace McMurtry (2019). (1st October 2020) - Chignell, Hugh
Review of: Revolution in the Echo Chamber: Audio Drama's Past, Present and Future, Leslie Grace McMurtry (2019)Bristol: Intellect, 294 pp., ISBN 978-1-78320-982-8, h/bk, £18.72